Climate change mitigation projections for ASEAN - Rasiah, Rajah; Al-Amin, Abul Quasem; Chowdhurry, Anwar Hossain; Ahmed, Ferdous; Zhang, Chen (Taylor & Francis, 2018)
This article analyses climate mitigation impact once the Association of Southeast Asian Nations (ASEAN) introduce their respective Intended Nationally Determined Contribution (INDC) using dynamic non-linear computable general equilibrium modelling and 2010 input-output tables. The results indicate that atmospheric concentration of carbon and temperatures under the business as usual (BAU) scenario will fall from 390 PPM and 0.80°C respectively in 2010 to 351PPM and 0.79°C respectively, whereas under the optimal scenario it will fall to 329PPM and 0.71°C respectively in 2060. Cumulative climate damage under BAU and optimal scenarios will remain the same at MYR8.0 Billion, MYR14.3 Billion and MYR 24.8 Billion respectively in 2010, 2015 and 2020 but it will rise after that to MYR579 Billion under the former compared to MYR513 Billion under the latter in 2060. The reduction in carbon emissions shall also be achieved without a tangible fall in GDP per capita.